Trade union activists, east and west : comparisons in multinational companies - Meardi, Guglielmo (Gower, 2000)
"This book examines the different perspectives of trade-union activists in western and eastern European countries following considerable changes which have taken place in the institutional and economic environments of both during the past decade or more. The research includes a large sample of interviews with activists and develops original and innovative frameworks against which to analyse the responses of these interviews. This text is well-rooted within a diversity of theoretical literature which will be relevant for courses on the sociology of work."--BOOK JACKET.